The Current Situation of Esophageal Cancer Staging and Perioperative Strategies Determination in Central and Southern China: A Cross Sectional Survey - Lu, Di; Liu, Xiguang; Feng, Siyang; Dong, Xiaoying; Shi, Xiaoshun; Ren, Pengfei; Diao, Dingwei; Wu, Hua; Xiong, Gang; Wang, Haofei; Li, Mei; Rao, Shuan; et al. (Frontiers in Oncology, 2019)
Purpose: We aim to investigate the current esophageal cancer staging according to the 7th edition TNM classification for esophageal carcinoma proposed by American Joint Committee on Cancer (AJCC) among oncology-related physicians in China. Methods: A specifically-designed 14-item questionnaire was distributed to 366 doctors who were working with esophageal cancer patients We collected and analyzed the feedbacks and explored the possible associations within different departments, including thoracic surgery, the internal medicine of gastroenterology, oncology, and/ radiotherapy in eight different hospitals from central and southern China. Results: Among all the responses, 31.42% of them were from thoracic surgery department, 40.44% were from oncology and/or radiation therapy and 28.14% were from the internal medicine of gastroenterology, respectively. Surprisingly, in total 66.12% of all the physicians were unaware that the 7th edition of esophageal carcinoma TNM classification was released in 2009; only 21.86% and 16.67% of physicians recognized cervical nodes and celiac nodes as regional lymph nodes. Furthermore, 67.21% physicians didn’t know that tumor location, histologic grade, and histopathology were accepted as new prognostic factors in the latest TNM system; and 51.37% physicians could not determine the correct TNM classification of esophagogastric junction cancers. Intriguingly, over 50% of them could still design appropriate perioperative strategies. Conclusions: The 7th edition of the TNM classification for esophageal carcinoma is poorly recognized and understood in central and southern China, which might contribute to the relatively low rates of appropriate perioperative procedures applied for esophageal cancer patients.